2018
DOI: 10.1089/jwh.2017.6564
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Health Knowledge, Attitudes, and Behaviors Among Women Enrolled in Medication-Assisted Treatment for Opioid Use Disorder

Abstract: Strategies to ensure all women enrolled in MAT for OUD have knowledge of effective contraception and affordable, quality contraception care that is responsive to their complicated and oftentimes traumatic histories are necessary to enhance the women's reproductive health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(43 citation statements)
references
References 36 publications
0
43
0
Order By: Relevance
“…Because a number of health characteristics have been found to be associated with unintended pregnancy, we examined whether participants had experienced any form of intimate partner violence (IPV) in the past six months, problem alcohol use in the past month (as indicated by an AUDIT‐C score of 3 or above, based on the frequency, timing and amount of drinking) and clinically relevant symptoms of depression or anxiety in the past week (from the Brief Symptom Inventory, as indicated by a score of 2 or above on the depression or anxiety subscale) . In addition, we assessed participants' level of stress using the Perceived Stress Scale and emotional social support using the Multidimensional Scale of Perceived Social Support (continuous scores were generated for each).…”
Section: Methodsmentioning
confidence: 99%
“…Because a number of health characteristics have been found to be associated with unintended pregnancy, we examined whether participants had experienced any form of intimate partner violence (IPV) in the past six months, problem alcohol use in the past month (as indicated by an AUDIT‐C score of 3 or above, based on the frequency, timing and amount of drinking) and clinically relevant symptoms of depression or anxiety in the past week (from the Brief Symptom Inventory, as indicated by a score of 2 or above on the depression or anxiety subscale) . In addition, we assessed participants' level of stress using the Perceived Stress Scale and emotional social support using the Multidimensional Scale of Perceived Social Support (continuous scores were generated for each).…”
Section: Methodsmentioning
confidence: 99%
“…Since the completion of this 2015 systematic review, there have been additional studies that indicate external condoms are still the most commonly used contraceptive by women with opioid use disorder. 5,7,8…”
Section: Contraceptive Behaviorsmentioning
confidence: 99%
“…Patient Beliefs and Knowledge Although most women with opioid use disorder have an awareness of and appreciation for contraceptive use, great variability in contraceptive knowledge may contribute to disparate levels of contraception initiation. 8 One study gauging reproductive health knowledge and attitudes of 283 women with opioid use disorder found that over 70% agreed or strongly agreed that it was important to avoid getting pregnant. Furthermore, women endorsed a high level of consideration for the increased perinatal risk posed by opioid use.…”
Section: Factors Affecting Contraceptive Accessmentioning
confidence: 99%
See 2 more Smart Citations